Using Multiblock Copolymers as Sacrificial Materials in 3D Printing Processes
Patent Information
- Application Number
- JP2023579478
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-10-07
- Filing Date
- 2022-06-15
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-06-15
Smart Images

Figure 0007642108000005 
Figure 0007642108000001 
Figure 0007642108000002
Abstract
Description
[Technical field]
[0001] The present invention relates to the use of multiblock copolymers or multiblock copolymer compositions as sacrificial materials for 3D fused deposition modeling. In the present invention, only block copolymers are used, which excludes any other polymers with a non-block copolymer-like architecture.
[0002] Such materials exhibit rapid solubility or dispersibility in a variety of solvents while possessing the perfect thermomechanical properties to create threads or rods that can be used to support the polymers (including those with high glass transition temperatures (Tg)) that make up the parts manufactured in 3D printing (fused deposition modeling) before being dissolved in the solvent and removed.
[0003] Three-dimensional printing (or 3D printing) allows additive manufacturing (or AM) of real objects based on virtual ones. 3D printing is based on cutting a 3D virtual object into 2D slices of very thin thickness. These thin slices are stacked one by one by fixing them on top of the previous slices to reconstruct the real object. The construction materials of the object include plastics, especially acrylonitrile butadiene styrene (or ABS) and polylactic acid (or PLA), as well as polyaryletherketones (PAEK), polyetherimides (PEI), waxes, metals, or ceramics. Examples of additive techniques are fused filament fabrication (FFF) and laser sintering.
[0004] Fused deposition modeling is a technique that consists of melting a filament through an extrusion nozzle. From this nozzle emerges a molten filament with a diameter of the order of one millimeter. This thread is laid down in a line and adheres by remelting onto the previously laid thread. This technique makes it possible to generate parts made of suitable materials that have mechanical and thermal properties and stability comparable to injection molded thermoplastic parts, but are often lighter. In the case of polymers, for mechanical reinforcement reasons, this technique requires supports to manufacture the parts, which are also extruded together. This construction support consists of a material separate from the material that constitutes the object to be generated, and once the construction process of the object is finished, this support is removed from the generated object.
[0005] The build supports are generally soluble or dispersible polymer compositions that meet very precise specifications. In addition to mechanical strength, the glass transition temperature of the copolymer (which must be similar to that of the material to be printed), thermal stability or processability, and kinetics of dissolution or dispersion in various solvents, especially water, are among the most important desired properties. If the dissolution or dispersion solvent is water, the material must also store well. This latter property is not always easy to produce, as water-soluble or water-dispersible compositions and filaments can prove difficult to store in humid atmospheres. During storage, caking of the granules and adhesion of the filament to the spool can be observed in the presence of ambient moisture. [Background technology]
[0006] This 3D printing technique requires support materials that allow the construction of complex parts, which are described, for example, in WO2010 / 045147. Other water-soluble support materials include: - Polyvinyl alcohol - Butenediol / vinyl alcohol BVOH copolymer - (meth)acrylic copolymers.
[0007] These supporting polymer compositions always contain multiple copolymers whose role is to adjust the solubility, mechanical properties or other parameters, making their development more difficult.
[0008] Other support materials that dissolve in other solvents include, for example, high impact polystyrene (HIPS), which dissolves in limonene.
[0009] It is known in the prior art that the support must have a glass transition temperature (Tg) relatively close to the Tg of the polymer that constitutes the object to be printed, within an order of magnitude lower than 10° C. from the Tg of the polymer that constitutes the object to be printed.
[0010] Without such a Tg, the support material will exhibit too much creep and therefore the printed part will not build up properly, as explained for example in US5866058.
[0011] Surprisingly, the applicant has found that when block copolymers are used as sacrificial supports, alone or in combination, this condition of close Tg of the printed material / support is no longer essential. This is advantageous since it opens up much more possibilities for defining other properties of the support polymer. Thus, it becomes easier to adjust other parameters, such as mechanical parameters and solubility parameters in aqueous media, without worrying about the Tg of the sacrificial support polymer, as long as the Tg of the sacrificial support polymer is lower than the Tg of the polymer that constitutes the object to be printed. Thus, in the case of a block copolymer with a maximum Tg of one of the blocks, for example 50°C, such a block copolymer can be used as a support material for building objects made of materials with Tg in the range of 50°C to 200°C. When combined with other block copolymers with at least one block with a glass transition temperature (Tg) below 0°C and at least one block with a Tg above 0°C, compositions with very good mechanical properties are obtained.
[0012] This opens up new possibilities for printing objects made from polyaryletherketones (PAEK), polyetherimides (PEI), polyamideimides (PAI), polysulfones (PSU), poly(ethersulfones) (PES) and poly(phenylene sulfide) (PPS), which have very limited options for sacrificial support polymers and other drawbacks. Summary of the Invention
[0013] Use of at least one multiblock copolymer (I) as a sacrificial material in a process for 3D printing a polymer having a Tg between 140 and 200° C., selected from PEEK, PEKK, PEI, PAI, PSU and PPS, wherein the at least one multiblock copolymer (I) comprises i monomers M randomly bonded together. i (i is an integer ranging from 2 to 5 inclusive), and j monomers M j (j is an integer ranging from 2 to 5 inclusive), i is selected from a monomer A having a homopolymer Tg of less than 0° C. and a hydrophilic monomer B, the mass ratio of A being in the range of 80% to 95% and the mass ratio of B being in the range of 5% to 20%, and M j is selected from monomer C having a homopolymer Tg of less than 0°C, monomer D having a homopolymer Tg of more than 25°C, and hydrophilic monomer E, and the mass proportions of monomers C, D and E are between 25-35%, 25-35% and 35-45%, respectively. [Brief description of the drawings]
[0014] [Figure 1] FIG. 2 shows the DMA behavior of sacrificial polymer (I) and the combination of said polymer (I) with copolymer (II) (sacrificial polymer + 5% M52N). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] There is every reason to believe that any type of monomer having the properties described in the Summary of the Invention and the associated proportion in the block copolymer (I) will provide advantageous behavior in solving the technical problems described in the Background of the Invention.
[0016] It does not predict the chemicals that may be used.
[0017] However, there are few chemistries available that allow the preparation of such structures in block copolymers.
[0018] The reactive blocks may be prepared, for example by polycondensation or ring opening, with the selection and proportion of monomers according to the invention overview, and in a second step other blocks can be attached.
[0019] The blocks can also be prepared by radical or anionic polymerization as well, ie block by block, allowing the stepwise attachment of other blocks, with the choice and proportions of monomers according to the inventive overview.
[0020] Among the preferred techniques, controlled radical polymerization is used since it is possible to obtain the block copolymers in successive steps within the same process operation.
[0021] Non-limiting examples include RAFT (Radical Addition Fragmentation Transfer) or NMP (Nitroxide Mediated Polymerization).
[0022] Preferably, NMP is selected, preferably NMP using the counter radical N-tert-butyl-1-diethylphosphono-2,2-dimethylpropyl nitroxide, which is widely described and used in the literature and is used in the form of an alkoxamine or polyalkoxamine of 2-([tert-butyl[1-(diethoxyphosphoryl)-2,2-dimethylpropyl]amino]oxy)-2-methylpropionic acid.
[0023] Concerning the monomers of the block copolymer (I) described in the Summary of the Invention, monomer A is selected from alkyl (meth)acrylates (wherein the alkyl has a linear or substituted C4-C18 chain, optionally containing oxygen), and in particular the following monomers: butyl acrylate (buA), 2-ethylhexyl acrylate (2EHA), methoxyethyl acrylate (MEA), lauryl methacrylate (lauMA), stearyl methacrylate (SMA).
[0024] Monomer B is selected from acrylic acid (AA), methacrylic acid (MAA), styrene sulfonate, 2-acrylamido-2-propanesulfonic acid.
[0025] Monomer C is selected from alkyl (meth)acrylates, where the alkyl has a linear or substituted C4 to C18 chain and optionally contains oxygen, and in particular the following monomers: butyl acrylate (buA), 2-ethylhexyl acrylate (2EHA), methoxyethyl acrylate (MEA), lauryl methacrylate (lauMA), stearyl methacrylate (SMA).
[0026] Monomer D is selected from styrene (S); methyl methacrylate (MMA), acrylonitrile (AN), isobornyl acrylate.
[0027] Monomer E is selected from acrylic acid (AA), methacrylic acid (MAA).
[0028] Preferably, A is butyl acrylate or 2-ethylhexyl acrylate, more preferably butyl acrylate, B is acrylic acid or methacrylic acid, C is butyl acrylate or 2-ethylhexyl acrylate, more preferably butyl acrylate, D is styrene, acrylonitrile, methyl methacrylate or isobornyl acrylate, more preferably styrene or isobornyl acrylate, and E is acrylic acid or methacrylic acid.
[0029] Polymers that can be printed using the sacrificial polymer composition of the present invention have a glass transition temperature (Tg) greater than 50° C., including, but not limited to, polylactic acid (PLA), acrylonitrile butadiene styrene (ABS), acrylonitrile styrene acrylonitrile (ASA), polyamide (PA), polycarbonate (PC), polymethyl methacrylate (PMMA), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), copolyesters such as polyolefins (PE, PP), and polymers with high Tg between 140-200° C., such as polyaryletherketones (PAEK) (PEEK, PEKK, PEK, PEKEKK, PEEKK, PEKK as above depending on the aryletherketone sequence), polyetherimide (PEI), polyamideimide (PAI), polysulfone (PSU), poly(ethersulfone) (PES), or poly(phenylene sulfide) (PPS).
[0030] The use of block copolymers as water-soluble support materials for high temperature polymers such as PEEK, PEKK, PEI, PAI, PSU and PPS is particularly useful. Other polymers with lower Tg mentioned can also be printed, but other solutions already exist.
[0031] Thus, the preferences of the present invention extend to the use of the block copolymers described in the Summary of the Invention to print polymers having a Tg between 50 and 200°C, preferably between 140 and 200°C.
[0032] The block copolymer (I) described in the Summary of the Invention is preferably a di- or triblock copolymer, more preferably a diblock copolymer. In the definition of these copolymers, i can have a value between 2 and 5, preferably between 2 and 3 (including the boundaries), more preferably 2. In the definition of these copolymers, j can have a value between 2 and 5, preferably between 2 and 3 (including the boundaries), more preferably 3.
[0033] In these copolymers, the proportion by mass of the block consisting of monomers of families A and B is in the range from 5% to 40%, preferably between 10% and 30% (block 1), and the proportion by mass of the block consisting of monomers C, D and E is in the range from 50% to 90%, preferably between 60% and 80% (block 2).
[0034] Due to the balance of properties associated with the selection of monomers selected in the present invention, these copolymers can be dissolved in a solvent selected from, but not limited to, water, DMSO, alcohols, or ketones, with water being the preferred solvent, in a pH range that can vary from 7 to 12, preferably 10 to 12.
[0035] In addition to the block copolymer (I) used in the present invention, the copolymer may be combined with at least one block copolymer (II).Accordingly, the present invention also relates to the use of the combination of copolymers (I) and (II) as a sacrificial material composition in a 3D printing process.
[0036] The block copolymer (II) is preferably a di- or triblock copolymer, more preferably a triblock copolymer, and is prepared by the same type of polymerization chemistry and process and following the same type of preferences with respect to polymerization chemistry and process as the block copolymer (I).
[0037] The copolymer (II) has at least one block having a glass transition temperature (Tg) below 0°C and at least one block having a Tg above 0°C.
[0038] As regards the monomers of the block copolymer (II), they are selected from the following: For blocks with a Tg below 0° C., butyl acrylate, 2-ethylhexyl acrylate, preferably butyl acrylate. For the blocks having a Tg above 0° C., methyl methacrylate, styrene, acrylic acid, methacrylic acid, dimethylacrylamide, isopropylacrylamide, isobornyl acrylate, preferably methyl methacrylate, dimethylacrylamide, isobornyl acrylate and isopropylacrylamide, in the case of dimethylacrylamide or isopropylacrylamide, the proportion by weight is between 1% and 30% by weight, preferably between 5% and 15% by weight, relative to the total of (II).
[0039] When the dissolution or dispersion medium is water, the compositions of the present invention, in the presence or absence of copolymer (II), show very good dissolution at high pH values, e.g. 12, and much less dissolution at pH 7. This provides the advantage that spools of yarn produced with these copolymers have better storage stability, especially in humid atmospheres.
[0040] The copolymers (I) described in the Summary of the Invention have a weight average molecular weight, measured by SEC using polystyrene standards, between 80,000 and 150,000 g / mol and a dispersity index between 1 and 3, preferably between 1.5 and 2.5.
[0041] In order to adjust specific properties, the copolymer (I) can be mixed with other block copolymers.
[0042] The block copolymer (II) has a weight average molecular weight, measured by SEC using polystyrene standards, between 50000 and 150000 g / mol and a dispersity between 1 and 3, preferably between 1.5 and 2.5.
[0043] These block copolymers (II) may be used in the composition in a proportion ranging from 1% to 50% by weight, preferably between 3% and 15% by weight, relative to the total weight of (I)+(II).
[0044] The glass transition temperature (Tg) is measured by DSC. EXAMPLES
[0045] Example 1 - Synthesis of Copolymer (I) P(BA-AA)-bP(BA-S-MAA) This example targets a diblock copolymer iMi-jMj (i=2, j=3) represented by mMnN-block-oOpPqQ.
[0046] Block 1: M: butyl acrylate (buA), m = 90% of block 1 N: acrylic acid (AA), n = 10% of block 1. Block 2: O: buA, o = 30% of block 2 P: styrene (S), p = 30% of block 2 Q: methacrylic acid (MAA), q=40% of block 2.
[0047] The synthesis of this diblock copolymer is carried out in two steps: The first block P(BA-AA) is synthesized in bulk and then stripped of unreacted monomers. The second block P(BA-S-MAA) is synthesized in solvent.
[0048] 1.1. Synthesis of Block P(BA-AA) This first block is synthesized by a bulk polymerization process using an Ingenieur Buro type reactor.
[0049] Reactants: - Butyl acrylate (BA) 208.7g - Acrylic Acid (AA) 22.9g - Block Builder(R) 2.51g The target conversion rate is 70% and the number average molecular weight is 27,000 g / mol.
[0050] The reactants are weighed, then mixed by magnetic stirring and then introduced into the reactor under vacuum pressure. The reactor is stirred (250 rpm). The medium is degassed by three alternating cycles of nitrogen pressure and vacuum. The polymerization is carried out in three temperature steps: 105°C for 60 min, then 110°C for 90 min. The polymerization time is 300 min. The conversion is monitored by dry extraction (thermobalance at 150°C and vacuum oven at 125°C) by taking samples every hour.
[0051] Once the target conversion is achieved, the temperature is reduced to 80°C. Once the set temperature is reached, the apparatus is gradually placed under reduced pressure to distill off the unreacted monomers (collected in a liquid nitrogen trap). The system is left at 80°C and maximum reduced pressure for approximately 90 minutes, and once the distillation is complete, the set temperature is reduced to 40°C and once this set temperature is reached, 160 g of toluene are introduced (under vacuum pressure) to dilute the medium. The system is left under stirring at 40°C for several hours to completely homogenize the solution. The solution is then collected.
[0052] 1.2. Synthesis of Block P(BA-S-MAA) The synthesis is carried out by the solvent method using a mixture of ethanol / toluene in a mass ratio of 60 / 40, with the synthesis being carried out at 45% solvent relative to the total raw materials.
[0053] A BA / S / MAA mixture in a mass ratio of 30 / 30 / 40 is introduced.
[0054] The copolymer P(BA-AA)-bP(BA-S-MAA) with a mass composition of 30 / 70 and a conversion of the second block of 70% is targeted.
[0055] The raw materials are prepared as follows. First block diluted with ethanol: 154.8 g BA / S / AMA:154.8 / 154.8 / 206.4(g) Ethanol / toluene: 329 / 219.5(g) The molar mass (PS equivalent) of this copolymer is as follows: Mp=95000g / mol Mn=53000g / mol Mw=95000g / mol PI=1.81
[0056] In Examples 2-4 (Invention 2-4), iMi-jMj diblock copolymers (i=2, j=3) represented as mMnN-block-oOpPqQ are prepared with the same block ratio and monomer ratio as in Example 1 under the same synthesis conditions. In Table 1, the following monomers are selected: Table 1 TIFF0007642108000001.tif35170
[0057] The proportions of m, n, o, p, q are the same as in Example 1. The polymer obtained has similar properties in that the molecular weight does not vary by more than 10% compared to the polymer obtained in Example 1.
[0058] Example 5: Dissolution Test The test is run until pellets of the support material of the present invention and the commercially available Aquasis® 120 and 180 products are completely dissolved.
[0059] The pellets are prepared by pressing at 200° C. The dissolution of the pellets is carried out at pH=7 and pH=12 at a temperature of 60° C.
[0060] Example 6: Filament Extrusion: Spools were formed directly from the material of the present invention.
[0061] The spinning is carried out using a single-screw "Labtech LBE20-30 / C" extruder (screw diameter: 20 mm). A caterpillar-type take-up machine is used to take up the rod at a constant speed (9.1-9.4 m / min).
[0062] The extruder and gear pump are adjusted to 190°C.
[0063] The extruder screw speed was 30-34 rpm and the pressure P = 55 bar.
[0064] The commercially available control products, Aquasis® 120 and Aquasis® 180, are available in spools of thread that can be used directly in 3D printing devices.
[0065] Example 7: 3D Printing The parts were printed on an "Original Prusa i3 MK3S+" 3D printer. Other available printers can also be used. Filamentous sacrificial resin according to the invention or Aquasis® 180 (control) is printed at a plate temperature of 250° C., with the first layer at 122° C., then the next layer at 120° C., at a speed of 40 mm / s. The layer height is 0.2 mm and the infill is 100% concentric.
[0066] Filamentous sacrificial resin according to the invention or Aquasis® 120 (control) is printed at a speed of 10 mm / s with a plate temperature of 220° C., the first layer at 120° C., then the next layer at 105° C. The layer height is 0.2 mm and the infill is 100% concentric.
[0067] The polymer resin of the part to be built is printed under the following conditions: ABS, 3DFilTech: 250℃; 10mm / s. PLA, eMotion TECH: 210℃; 10mm / s. PEI: ThermaX PEI-Ultem 9085: 360℃; 10mm / s. PEKK, ThermaX PEKK 3DXTech: 360℃; 10mm / s.
[0068] The parts built are 4 cm x 1 cm x 0.5 cm sacrificial polymer bars (invention and control) on which a bar of the same dimensions is built using the target polymer (PLA, ABS, PEKK, PEI, etc.).
[0069] Example 8: The part is built and, depending on the use of a control sacrificial resin with the given polymer being printed or a sacrificial resin of the invention if possible, the whole is immersed in 60°C water with a pH of 7 or 12, and then the time until all the sacrificial material is dissolved is recorded. If the test is judged to be a failure, this means that the part being built does not conform to the desired 3D digital model.
[0070] The results of the dissolution test and 3D printing test are shown in Table 2. Table 2 TIFF0007642108000002.tif58170T1: Time (min), total dissolution at 60°C, water pH 7 T2: Time (min), total dissolution at 60°C, water pH 12
[0071] From Table 2, it can be seen that no matter what polymer is being printed, the sacrificial resin of the present invention is capable of supporting the printed polymer.
[0072] Example 9: The mechanical properties of the sacrificial polymer of invention 1, with and without the addition of copolymer (II), were evaluated by tensile tests.
[0073] The measurements are carried out on filaments with a length of 14 cm and a diameter of 1.75 mm. The breaking elongation is measured using a "Zwick Roell Z005" type instrument with a 5 kN sensor, speed: 5 mm / min, grip distance = 61 mm.
[0074] The copolymers (II) tested are commercially available under the name Nanostrength®, references M52N and M65N. These copolymers meet the description of copolymer (II) in terms of composition and molecular weight. These copolymers are added in amounts of 5% and 10% by weight.
[0075] Table 3 shows the evaluations that were performed. Table 3 TIFF0007642108000003.tif48170
[0076] It can be seen that the addition of copolymer (II) on the one hand improves the elongation at break and on the other hand this elongation is maintained even after one month of storage.
[0077] Dissolution of a portion of the material of Example 9 in the presence and absence of copolymer (II) was performed at 60° C. and pH 12 and shows that the presence of copolymer (II) has only a slight detrimental effect, as shown in Table 4. Table 4 TIFF0007642108000004.tif31170
[0078] The materials of Example 1 (I) and Example 9 (I+II) with 5% M52N were investigated by DMA (Dynamic Mechanical Analysis). Curve 1 shows that the rheological behavior of the two materials is very similar.
Claims
1. Use of at least one multiblock copolymer (I) as a sacrificial material in a process for 3D printing a polymer having a Tg between 140 and 200° C. selected from PEEK, PEKK, PEK, PEKEKK, PEEKK, PEKK, PEI, PAI, PSU and PPS, wherein the at least one multiblock copolymer (I) is composed of i monomers M randomly bonded. i (i is an integer ranging from 2 to 5 inclusive), and j monomers M j (j is an integer ranging from 2 to 5 inclusive), i is selected from a monomer A having a homopolymer Tg of less than 0° C. and a hydrophilic monomer B, the mass percentage of A being in the range of 80% to 95% and the mass percentage of B being in the range of 5% to 20%, and M j is selected from monomer C having a homopolymer Tg of less than 0° C., monomer D having a homopolymer Tg of more than 25° C., and hydrophilic monomer E, the mass proportions of monomers C, D and E being between 25-35%, between 25-35% and between 35-45%, respectively.
2. 2. Use according to claim 1, in which the at least one block copolymer (II) is present in a proportion by weight between 1% and 50% by weight relative to the total weight of (I)+(II).
3. 3. The use according to claim 1 or 2, wherein at least one block copolymer (I) is a diblock or triblock copolymer.
4. 4. The use according to claim 3, wherein the block copolymer (I) is a diblock copolymer.
5. 5. The use according to claim 4, wherein the diblock copolymer (I) has a mass proportion of the block consisting of monomers of families A and B in the range from 5% to 40% (block 1) and a mass proportion of the block consisting of monomers C, D and E in the range from 50% to 90% (block 2).
6. 2. The use according to claim 1, wherein the copolymer (II) has at least one block with a glass transition temperature below 0°C and at least one block with a glass transition temperature above 0°C.
7. 3. The use according to claim 1 or 2, wherein the block copolymer is prepared by controlled radical polymerization.
8. The use according to claim 7, wherein the block copolymer is prepared by nitroxide-mediated radical polymerization.
9. The use according to claim 8, wherein the block copolymer is prepared by radical polymerization mediated by N-tert-butyl-1-diethylphosphono-2,2-dimethylpropyl nitroxide.
10. 9. The use according to claim 8, wherein at least one block copolymer (I) consists of a block 1 with butyl acrylate and acrylic acid and a block 2 with butyl acrylate, styrene and methacrylic acid.
11. 2. The use according to claim 1, wherein at least one block copolymer (I) has a weight average molecular weight between 80000 g / mol and 150000 g / mol.
12. 3. Use according to claim 2, in which the copolymer (II) has a weight average molecular weight between 50000 g / mol and 150000 g / mol.
Citation Information
Patent Citations
Water-soluble block copolymers and their use as support materials for 3D printing
JP2017538607A
Water-soluble diblock copolymer
JP2017538846A
Soluble material for three-dimensional molding
JP2019064258A
Organic microgel system for 3D printing of silicone structures
US20180057682A1
Sacrificial high heat support materials for additive manufacturing processes
US20190193336A1